An empirical investigation of corporate social responsibility by Malaysian public listed companies a panel data approach - Abdul Hamid, Fathilatul Zakimi; Abdul Rahman, Azhar; Che Ahmad, Ayoib; Ismail, Mohamad Sharofi (Universiti Utara Malaysia, 2004)
This paper explores the level of social disclosure among the top 100 Malaysian listed companies. This study focuses on Malaysian companies because the Malaysian stock market is considered to be one of the largest stock market in terms of market capitalization in the Asia. Furthermore prior related empirical work largely focused on Western and developed countries. The main contribution of this study is the introduction of panel data analysis as opposed to traditional cross sectional analysis to demonstrate its potential to improve estimation. The panel data analysis shows that size and industry classification appears significantly influence to the disclosure practice. Moreover, legitimacy theory can be employed to explain the differences related to CSR disclosure theme, size and individual membership. However, weak relationship for profitability, age incorporated and government ownership against CSR disclosure. The implication of these findings may be explored in further research.